2010
DOI: 10.2174/1874104501004010003
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of D-Amino Acid Oxidase (DAAO) Inhibitors

Abstract: BackgroundHealth care professionals worldwide attend courses and workshops to learn evidence-based medicine (EBM), but evidence regarding the impact of these educational interventions is conflicting and of low methodologic quality and lacks generalizability. Furthermore, little is known about determinants of success. We sought to measure the effect of EBM short courses and workshops on knowledge and to identify course and learner characteristics associated with knowledge acquisition.MethodsHealth care professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
(30 reference statements)
1
26
0
Order By: Relevance
“…Therefore, it is likely that repeated administration of SB increases D-serine levels in the brain, although a further study is needed to confirm this. Although DAAO inhibitors were proposed as new therapeutic drugs for schizophrenia, their clinical use has been largely unsuccessful (54,55). Ferraris et al (43) reported 5-chloro-benzo[d]isoxazol-3-ol (CBIO; IC 50 = 1680 nM) as being a more potent DAAO inhibitor than SB (Ki≈16 μM).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that repeated administration of SB increases D-serine levels in the brain, although a further study is needed to confirm this. Although DAAO inhibitors were proposed as new therapeutic drugs for schizophrenia, their clinical use has been largely unsuccessful (54,55). Ferraris et al (43) reported 5-chloro-benzo[d]isoxazol-3-ol (CBIO; IC 50 = 1680 nM) as being a more potent DAAO inhibitor than SB (Ki≈16 μM).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the forebrain, DAAO is predominantly expressed in neurones and, in rat models, DAAO was demonstrated to interact with (and to be inhibited by) bassoon protein in the presynaptic zone: this interaction would fine‐tune the d ‐serine concentration at the synapse, consequently affecting NMDAR activity . Because alteration of the cellular concentration of the neuromodulator d ‐serine has been related to schizophrenia, and inhibition of hDAAO by specifically designed inhibitors did not yield an increase in the neuromodulator concentration, the modulation of hDAAO inhibition by pLG72 might represent a novel mechanism for promoting therapeutic approaches targeting the molecular pathogenesis rather than the symptoms of this ‘mental’ disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is well acknowledged in the KT literature that one of the most difficult things to assess is the actual impact of new knowledge on specific policies or practices, or, ultimately, on health-related outcomes [34,75]. We have used a highly focused approach to assess the uptake and representation of a specific new research report in a range of documents, from news reports to national guidelines embedded in legislation.…”
Section: Discussionmentioning
confidence: 99%